Implementasi Metode Viola-Jones dan Eigenfaces Pada Sistem Pengenalan Wajah Secara Real-Time - La Ode, Abdul Azis Syah; Ningrum, Ika Purwanti; Saputra, Rizal Adi (Algoritme Jurnal Mahasiswa Teknik Informatika, 2024)
The application of face recognition technology in CCTV systems has become an important topic in improving security and efficiency in various sectors. This research examines the Viola-Jones and Eigenface methods for real-time face detection and recognition using CCTV. The Viola-Jones method is used for initial face detection with Haar features, while Eigenface is used for face recognition based on principal component analysis (PCA). This research involves capturing images from two CCTV camera positions with variations in lighting and distance. The test results show variations in recognition results between individuals at various light conditions and camera distances. Despite challenges such as lighting and viewing angle variations, this method provides a success percentage of up to 73.68% in face recognition under optimal conditions. The integration of this technology is expected to make a significant contribution in improving security and efficiency in various sectors, with a note of the need to pay attention to important privacy and data security aspects in its application.